2014
DOI: 10.1016/j.bbamcr.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Human erythrocyte band 3 functions as a receptor for the sialic acid-independent invasion of Plasmodium falciparum. Role of the RhopH3–MSP1 complex

Abstract: Plasmodium falciparum takes advantage of two broadly defined alternate invasion pathways when infecting human erythrocytes: one that depends on and the other that is independent of host sialic acid residues on the erythrocyte surface. Within the sialic acid-dependent (SAD) and sialic acid-independent (SAID) invasion pathways, several alternate host receptors are used by Plasmodium falciparum based on its particular invasion phenotype. Earlier, we reported that two putative extracellular regions of human erythr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 62 publications
0
35
0
Order By: Relevance
“…Band 3, which is defined here as potential erythrocyte receptor for PvTRAg38, is also known to interact with a number of known and unknown P. falciparum proteins and plays a crucial role in host cell invasion (29,(31)(32)(33)(34)(35)(36). This is based on the fact that the monoclonal antibodies against Band 3 blocked the invasion of rhesus monkey erythrocytes by the Plasmodium knowlesi merozoites in a primate model (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Band 3, which is defined here as potential erythrocyte receptor for PvTRAg38, is also known to interact with a number of known and unknown P. falciparum proteins and plays a crucial role in host cell invasion (29,(31)(32)(33)(34)(35)(36). This is based on the fact that the monoclonal antibodies against Band 3 blocked the invasion of rhesus monkey erythrocytes by the Plasmodium knowlesi merozoites in a primate model (37).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that PfMSP1 forms complex with RhopH3, as well as with PfMSP9, to interact with 5ABC (defined here as B3F5 fragment) and 6A of Band 3 (29,31,34). In that case, the cooperative binding of several parasite proteins (the PvTRAg38, MSP 1, MSP9, and maybe other additional proteins) to the same host erythrocyte receptor through its different exofacial regions may be providing the parasite an opportunity to tighten its interaction with the host cell.…”
Section: Discussionmentioning
confidence: 99%
“…33 Consistent with these findings, our previous work showed that MSP1 19 interacts with host band 3 receptor, mediating parasite invasion of RBCs via the sialic acid-independent invasion pathway. 12,13,41 Host band 3 is the most abundant membrane protein in RBCs and forms a tight stoichiometric complex with GPA. Like band 3, GPA is also highly abundant and serves as a sialic acid-dependent receptor, binding the parasite ligand EBA-175.…”
Section: Discussionmentioning
confidence: 99%
“…12,13,41 Host band 3 is the most abundant membrane protein in RBCs and forms a tight stoichiometric complex with GPA. Like band 3, GPA is also highly abundant and serves as a sialic acid-dependent receptor, binding the parasite ligand 42 On the basis of these observations, we hypothesized that merozoites may display ligands that can potentially bind to band 3 and GPA simultaneously, thus integrating distinct invasion pathways.…”
mentioning
confidence: 99%
“…The phenomenon of red cell invasion by merozoites of Plasmodium is highly complex because parasites use multiple invasion pathways thus utilizing large numbers of parasite ligands and their respective receptors on host erythrocytes. Complexity is further increased when the individual parasite ligand interacts with more than one erythrocyte receptor, and similarly, each erythrocyte receptor is recognized by more than one parasite ligand (4,14,(27)(28)(29). The numbers of erythrocyte receptors identified for the P. vivax merozoite proteins is very limited (3,10,12).…”
Section: Discussionmentioning
confidence: 99%